China and the environment : the green revolution - Geall, Sam.; Hilton, Isabel (London : Zed Books, 2013)
The trajectory of China's growth is leading many environmentalists t o ask how the state and its people really engaging with environmental i ssues? This book provides access to otherwise unknown stories of enviro nmental activism and forms the first real-life account of China and its environmental tensions. China and Environment provides a unique report on the experiences of participatory politics that have emerged in resp onse to environmental problems, rather than focusing only on macro-leve l ecological issues and their elite responses. Featuring previously unt ranslated short interviews, extracts from reports and other translated primary documents. The authors argue that going green in China isn't ju st about carbon targets and energy policy; China's grassroots green def enders are helping to change the country for the better.
Introduction: The return of Chinese civil society / Isabel Hilton -- 1. China's environmental journalists : a rainbow confusion / Sam Geall -- 2. The birth of Chinese environmentalism : key campaigns / Olivia B oyd -- 3. The Yangzonghai case : struggling for environmental justice / Adam Moser -- 4. Alchemy of a protest : the case of Xiamen PX / Jonath an Ansfield -- 5.Defending Tiger Leaping Gorge / Liu Jianqiang.
Includes bibliographical references and index.
Keywords: Environmentalism -- China; Environmental policy -- China; Pollution -- China